IRON ORE MINING GEOMECHANICAL PROBLEMS IN UKRAINE - Popov, S. O.; Timchenko, R. A.; Yerina, O. O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper deals with problems in Ukrainian iron ore mining industry resulted from enterprises reaching deep levels of mining. There are also described main causes of hazardous situations due to geomechanical factors at such depths, dynamic forms of excessive rock pressure manifestations, and types of external factors affecting the state and behavior of load-bearing elements of mining and technological objects below the surface to enable mining operations. The paper provides recommendations on creating a specialized geomecanics support system for mining enterprises which is based on labour safety risk-management principles as well as it presents geomechanics tasks to be solved by the system.
Keywords: geomechanics; problems; iron ores; mining industry